The Role of Local Government in Non-Structural Mitigation of Hydrometeorological Disasters for Tourism Infrastructure Resilience in Batam City - Nurfa, Sherly Arianti; Adi Subiyanto; Yuli Subiakto (International Journal of Technology and Education Research, 2026)
Hydrometeorological disasters are the most dominant type of disasters in Indonesia and have been increasing due to climate change. Batam City, as an archipelagic region highly dependent on the tourism sector, faces significant risks to infrastructure disruption caused by such disasters. This study aims to analyze the role of local government in non-structural mitigation and its implications for the resilience of tourism infrastructure. This research employs a qualitative approach using descriptive-analytical methods based on literature review and policy analysis. The findings indicate that local governments play a strategic role in regulatory formulation, institutional capacity building, public education, and cross-sectoral coordination. However, the implementation of non-structural mitigation still faces several challenges, including limited resources, weak inter-agency coordination, and low public participation. This study recommends strengthening disaster risk governance through collaborative approaches and integrating mitigation policies into tourism development planning to enhance sustainable infrastructure resilience.